THE UTILITY OF PROCESS AND COMPETENCY MANAGEMENT IN THE DEVELOPMENT OF A BALANCED SCORECARD: THE EXPERIENCE OF THE PORT AUTHORITY OF VALENCIAVALENCIAPORT - Fillol, Arturo Giner; Dickinson, Yoaima; Feliu, Vicente M. Ripoll (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2011)
Resumo ABSTRACT The aim of this article is to carry out an analysis of the accounting tools implemented in the Port Authority of Valencia and so, determine whether improvements in management can be achieved if the level of efficiency is established with attainable targets as a consequence of opportune and reliable information in Management Accounting. In this article we analyse how the use of a Balanced Scorecard has helped Port Authorities from the Spanish State Port System to implement their strategic Plan. The Port Authorities have become reliant on the Competency Management model as an instrument for strategic planning of human resources and also in the progressive use of Process Management, which aims to meet the objectives established in the Strategic Plan. On this premise, we set out how the above-mentioned Port Authority can fulfil specific strategic and operational objectives regarding the efficiency and effectiveness of the services they provide. Keywords: Balanced Scorecard; Management Accounting; Competency Management; ProcessManagement. RESUMEN El trabajo tiene como objeto realizar un análisis de las herramientas de Contabilidad de Gestión implantadas en la Autoridad Portuaria de Valencia, efectuando un análisis en virtud del cual se pueda determinar que si el nivel de eficiencia se establece con objetivos alcanzables, se consiguen mejoras en la gestión, como consecuencia de una oportuna y fiable información de la Contabilidad de Gestión. En el artículo se analiza como con la utilización del Cuadro de Mando Integral las Autoridades Portuarias del Sistema Portuario de Titularidad Estatal español, se han apoyado para la puesta en marcha sus Planes Estratégicos. Las Autoridades Portuarias se han venido apoyando en el modelo de Gestión por Competencias como instrumento para la planificación estratégica de los recursos humanos así como en la progresiva implantación de la Gestión por Procesos con objeto de dar cumplimiento a los objetivos previstos en el Plan Estratégico. De esta forma se expone cómo en la Autoridad Portuaria de Valencia, se puede conseguir el cumplimiento de determinados objetivos estratégicos y operativos relacionados con la eficiencia y eficacia en las operaciones de los servicios prestados. Palabras Clave: Contabilidad de Gestión; Cuadro de Mando Integral; Gestión por Competencias;Gestión por Procesos.